Impact on colorectal cancer mortality of screening programmes based on the faecal immunochemical test. Issue 5 (1st September 2014) - Zorzi, Manuel; Fedeli, Ugo; Schievano, Elena; Bovo, Emanuela; Guzzinati, Stefano; Baracco, Susanna; Fedato, Chiara; Saugo, Mario; Dei Tos, Angelo Paolo
Abstract : Objective: Colorectal cancer (CRC) screening programmes based on the guaiac faecal occult blood test (gFOBT) reduce CRC-specific mortality. Several studies have shown higher sensitivity with the faecal immunochemical test (FIT) compared with gFOBT. We carried out an ecological study to evaluate the impact of FIT-based screening programmes on CRC mortality. Design: In the Veneto Region (Italy), biennial FIT-based screening programmes that invited 50–69-year-old residents were introduced in different areas between 2002 and 2009. We compared CRC mortality rates from 1995 to 2011 between the areas where screening started in 2002–2004 (early screening areas (ESA)) and areas that introduced the screening in 2008–2009 (late screening areas (LSA)) using Poisson regression models. We also compared available data on CRC incidence rates (1995–2007) and surgical resection rates (2001–2012). Results: Before the introduction of screening, CRC mortality and incidence rates in the two areas were similar. Compared with 1995–2000, 2006–2011 mortality rates were 22% lower in the ESA than in the LSA (rate ratio (RR)=0.78; 95% CI 0.68 to 0.89). The reduction was larger in women (RR=0.64; CI 0.51 to 0.80) than in men (RR=0.87; CI 0.73 to 1.04). In the ESA, incidence and surgery rates peaked during the introduction of the screening programme and then returned to the baseline (2006–2007 incidence) or dropped below initial values (surgery after 2007). Conclusions: FIT-based screening programmes were associated with a significant reduction in CRC mortality. This effect took place much earlier than reported by gFOBT-based trials and observational studies.